The Effect of Supply Chain Integration and Competitive Advantage on Supermarket Operational Performance in Ambon City - Zainuddin Latuconsina (Training & Research Institute - Jeramba Ilmu Sukses, 2021)
This study aims to analyze the effect of supply chain integration on operational performance, and also to analyze the effect of competitive advantage on operational performance. The sample used in this study were 42 managers/heads of the supermarket production division in Ambon City. The data analysis technique used is Partial Least Square (PLS). The results show that supply chain integration has a positive effect on operational performance, the results also show that competitive advantage has a positive effect on operational performance.